Cottonscope fiber maturity, fineness, and ribbon width measurements with different sample sizes. Issue 9 (June 2015) - Rodgers, James; Naylor, Geoffrey RS; Cui, Xiaoliang; Delhom, Chris; Hinchliffe, Doug
The accurate and precise measurement of cotton maturity and fineness is often difficult, laborious, and/or expensive to perform. The Cottonscope® rapidly, accurately, and precisely measures fiber maturity and fineness with small quantities of sample (approximately 50 mg). Interest has been expressed in the use of different sample weights of fiber, especially lower sample weights by geneticists. A program was implemented to establish the capabilities of the Cottonscope to rapidly and accurately measure maturity (maturity ratio (MR), original polarized light microscopy maturity ratio (MRBF)), fineness, and ribbon width with different sample weights of fiber. The change in sample weight significantly impacted the Cottonscope results for MR, fineness, and ribbon width. Fineness was most impacted by varied sample weight. The impacts of sample weights on the cotton results were removed by re-calibrating the instrument at each sample weight. Decreasing the sample weight below 50 mg increased sample measurement times, especially at 10 mg sample weight. These results demonstrated that the Cottonscope can accurately and precisely measure the fiber's maturity, fineness, and ribbon width with cotton fiber samples as small as 10 mg.